Respuesta :

Answer:  See below

Step-by-step explanation:

-3    2^x + 3 = 2^(-3) + 3 = 0.125 + 3 = 3.125      (-3, 3.125)

-2    2^x + 3 = 2^(-2) + 3 = 0.25 + 3 = 3.25         (-2, 3.25)

-1    2^x + 3 = 2^(-1) + 3 = 0.5 + 3 = 3.5                (-1, 3.5)

0    2^x + 3 = 2^(0) + 3 = 1 + 3 = 4                        (0, 4)

1   2^x + 3 = 2^(1) + 3 = 2 + 3 = 5                          (1, 5)

2    2^x + 3 = 2^(2) + 3 = 4 + 3 = 12                      (2, 12)

3    2^x + 3 = 2^(3) + 3 = 8 + 3 = 11                       (3, 11)

ACCESS MORE

Otras preguntas